Sex estimation and sexual dimorphism analysis through hand anthropometry: Insights from a cross-sectional study - M.O. Suleiman; B. Danborno; S.A. Musa; J.A. Timbuak; A.O. Yusuf; H.O. Suleiman (Forensic Science International: Reports)
One crucial aspect of a forensic procedure is sex estimation during individual identification. Hand and its remains are usually among the common body parts found in scenes of mass disasters during forensic investigations. Hand outlines are also important in several biomedical fields such as prosthetics, plastic surgery, and ergonomics. This cross-sectional study was done to investigate sexual dimorphism and discriminate sex using hand and hand print dimensions of 283 male and 317 female subjects who were randomly selected. Bare hand measurement and bilateral hand prints were obtained using Vernier caliper, inked pad, and A4 plain paper. Data obtained were analyzed using SPSS version 23.0 IBM. Sexual dimorphism in all the hand dimensions and prints of both hands were observed. The binary logistic regression model showed that in the left hand, bare left-hand breadth (BLHB) was the single best variable to discriminate sex with a percentage accuracy of 69.5 %. Bare right-hand breadth (BRHB) was the best predictor in the right hand with a percentage accuracy of 71.8 %. The predicted probabilities of the binary logistic model (BLR) for the variables that contributed best to the prediction were analyzed using the receiver operating characteristic (ROC) curve. It was observed that the BLHB and BRHB had the highest area under the curve (above 0.5) in the hand and print variables respectively. Sexual dimorphism and sex determination were established in this study using hand dimensions and prints. The BLHB and BRHB were the best sex determinants in this study. Although the accuracies of sex estimation from both hands in this study are low, it does confirm and support previous reports of handbreadth being the best variable for sex estimation.